Upper Endoscopy up to 3 Years Prior to a Diagnosis of Gastric Cancer Is Associated With Lower Stage of Disease in a USA Multiethnic Urban Population, a Retrospective Study - Shailja C. Shah; Chiaki Nakata; Alexandros D. Polydorides; Richard M. Peek; Steven H. Itzkowitz (Korean Society for Preventive Medicine, 2019)
Objectives: In the USA, certain races and ethnicities have a disproportionately higher gastric cancer burden. Selective screening might allow for earlier detection and curative resection. Among a USA-based multiracial and ethnic cohort diagnosed with non-cardia gastric cancer (NCGC), we aimed to identify factors associated with curable stage disease at diagnosis. Methods: We retrospectively identified endoscopically diagnosed and histologically confirmed cases of NCGC at Mount Sinai Hospital in New York City. Demographic, clinical, endoscopic and histologic factors, as well as grade/stage of NCGC at diagnosis were documented. The primary outcome was the frequency of curable-stage NCGC (stage 0-1a) at diagnosis in patients with versus without an endoscopy negative for malignancy prior to their index exam diagnosing NCGC. Additional factors associated with curable-stage disease at diagnosis were determined. Results: A total of 103 racially and ethnically diverse patients were included. Nearly 38% of NCGC were stage 0-Ia, 34% stage Ib-III, and 20.3% stage IV at diagnosis. A significantly higher frequency of NCGC was diagnosed in curable stages among patients who had undergone an endoscopy that was negative for malignancy prior to their index endoscopy that diagnosed NCGC, compared to patients without a negative endoscopy prior to their index exam (69.6% vs. 28.6%, p=0.003). A prior negative endoscopy was associated with 94.0% higher likelihood of diagnosing curable-stage NCGC (p=0.003). No other factors analyzed were associated with curable-stage NCGC at diagnosis. Conclusions: Endoscopic screening and surveillance in select high-risk populations might increase diagnoses of curable-stage NCGC. These findings warrant confirmation in larger, prospective studies.